Citizen participation as an axis of social development in the community (Ágora de Heterodoxias, 2017)
Citizen participation is a right and a constitutional duty that needs to be especially attended from the academy where support tools can be provided for the formation of community organizations that are structured in favor of solving problems of life in society.   Hence, the present article reveals the highlights of the research called Citizen Participation as the Axis of Social Development in “Represa de El Guapo” Community in the municipality of Paez in Miranda state, Venezuela. In this investigation qualitative methods and techniques were used specifically from the phenomenology.  Participant interviews and observations were used to collect data with a sampling of extreme cases where four members of the Comunal Council from the referred community were the informants. Validity of the data was addressed through triangulation, prolonged stay of the researchers in the context and rechecking with the subjects. Categorization, content analysis and triangulation were considered as techniques for the analysis of information. As a result of the derivation made to the significant findings, a theoretical approach emerged in relation to Citizen Participation as the axis of Social Development in the referred community, highlighting the first as a set of operational relations constituted by a complex system of interrelations that defines it, and which is characterized by three basic processes that complement each other; cooperation, contribution and intervention, which can become a gateway to the total system.
Keywords: citizen participation; social development; community